Increasing the Human Resources Capacity of the LazisMu Pajangan Service Office - Muhammad Eko Atmojo (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2024)
Along with the development of the Muhammadiyah organisation, especially the Muhammadiyah Branch Leadership in Pajangan, it was only natural for organisational management and human resource capacity building to be enhanced. Since before the pandemic, the Muhammadiyah organisation in the Pajangan area has been rapidly growing, with one of the developments being the emergence of autonomous Muhammadiyah organisations. Some autonomous organisations that had begun to emerge include the Muhammadiyah Youth, LazisMu, and Nasiyatul Aisiyah. Therefore, competent human resources were needed to develop these organisations, one of which was at the LazisMu Pajangan Office. This community service activity would utilise the Participatory Rural Appraisal (PRA) approach, which involves community participation in the development process of an activity. The activities to be carried out in this regard included conducting group discussion forums, providing training for the LazisMu Service Office managers, upgrading financial management with direct guidance from the LazisMu Regional Office in Bantul, and branding the service office through social media. The activity was conducted from January to March 2023, and the training participants were approximately eight daily managers of the LazisMu service office in Pajangan. Based on the community service activity results, it could be concluded that the LazisMu service office managers in Pajangan understood how to manage administration in the service office. This was because the training provided positively impacted the office managers, especially in understanding the flow and administration bookkeeping in LazisMu services.